2007
DOI: 10.1038/sj.ejcn.1602839
|View full text |Cite
|
Sign up to set email alerts
|

Changes in weight and waist circumference over 9 years in a Scottish population

Abstract: Objective: To document patterns of measured weight and waist circumference (WC) change and the increase in overweight and obesity over a 9-year period. Subjects/Methods: A total of 1044 subjects from two age-defined cohorts aged 39 and 59 in 1991. Height, weight and WC were measured in 1991, 1995 and 2000 and body mass index (BMI) was calculated. Pattern of weight and WC change was studied over approximately 9 years. Results: The prevalence of overweight and obesity increased markedly and the younger cohort sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 18 publications
(27 reference statements)
5
23
0
Order By: Relevance
“…In Scotland, 1.4% of men and 3.5% of women reach BMI O40 kg/m 2 (12). Longitudinal studies have shown that the fastest weight increases were in young adults with little increase beyond the 5th decade (8,13). This pattern may change as the obesity epidemic progresses.…”
Section: Introductionmentioning
confidence: 99%
“…In Scotland, 1.4% of men and 3.5% of women reach BMI O40 kg/m 2 (12). Longitudinal studies have shown that the fastest weight increases were in young adults with little increase beyond the 5th decade (8,13). This pattern may change as the obesity epidemic progresses.…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal cohort studies in the United States (2-4), the United Kingdom (5), and elsewhere (6,7) testify to an inexorable rise in adiposity. The health consequences are unlikely to be trivial.…”
mentioning
confidence: 99%
“…Several research groups, mainly using population studies of weight gain in adults over time, have estimated the energy gap that may underlie the increases in body weight and obesity that have been observed globally 21 , 22 , 23 , 24 . Estimates of the daily energy excess in these studies ranged from 0.02 MJ/day in Swedish men 23 to 0.25 MJ/day at the 90th percentile for adults in the US 21 .…”
Section: Resultsmentioning
confidence: 99%